Estimated errors in |Vcd|/|Vcs| from semileptonic D decays - RYAN, SINEAD MARIE (Elsevier, 1999)
We estimate statistical and systematic errors in the extraction of the CKM ratio |Vcd|/|Vcs| from exclusive D-meson semileptonic decays using lattice QCD and anticipated new experimental results.
PUBLISHED
Keywords: Pure & Applied Mathematics